The Trade-off Between Efficiency and Learning in Interorganizational Relationships for Product Development - Sobrero, Maurizio; Roberts, Edward B. (Management Science, 2001)
This paper analyzes the performance implications of interorganizational relationships in the development of technological innovations, focusing on the characteristics of the tasks partitioned between a manufacturer and its suppliers in the development of new products. We identify two critical dimensions: (1) the design scope and (2) the level of task interdependency. The design scope dimension characterizes the type of problem-solving activities outsourced by the manufacturer. The level of task interdependency dimension characterizes the influence of any given supplier-manufacturer interaction on other activities within an overall innovation process. Data analyses on 50 supplier-manufacturer relationships drawn from three new product development projects show that the type of problem-solving activities being partitioned and their level of interdependency with the rest of the project are important predictors of performance outcomes of the relationship, controlling for contractual differences. Further, the analyses demonstrate a clear trade-off between short-term efficiency-increasing and longer-term learning-enhancing outcomes.